Keefektifan Model Problem Based Learning Dalam Pembelajaran Menulis Cerpen Siswa Kelas IV SD Inpres Andi Tonro Makassar - Magfirah Magfirah; H. Yuddin; Nur Khadijah Razak (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to describe the short story writing ability of class IV students at SD Inpres Andi Tonro Makassar through the Problem Based Learning model and to describe the effective Problem Based Learning learning model applied in writing short stories for class IV students at SD Inpres Andi Tonro Makassar. This research uses the one group pretest-posttest design research method. The population in this study were all students in class IVA and class IVB at SD Inpres Andi Tonro Makassar. The sampling technique used is a data source retrieval technique with certain considerations with experimental class and control class samples. The instrument used is a test instrument in the form of essay questions to measure students' short story writing results using the Pretest - Posttest. Based on the research results, it shows that students' ability to write short stories after using the Problem Based Learning learning model in the experimental class is in the high category, namely a posttest result of 90.42. Meanwhile, the average score of the control class posttest results was in the low category, 72.50. It is proven in the management results of the hypothesis that Sig (2. Tailed) = 0.000, meaning that H_0 is rejected because Sig (2. Tailed) < α or (0.000 < 0.05). H_1 is accepted because Sig (Tailed) > α or (0.596 > 0.05). In the analysis of the T Sig <t_tabel or (0.596 <1.746) test, it is concluded that H_0 is rejected and H_1 is accepted, meaning that there is significant effectiveness of the Problem Based Learning model in learning to write short stories for fourth grade students at SD Inpres Andi Tonro Makassar.